Effects of the Preheating Temperature on the Crystal Structure and Texture of Martensitic Stainless Steel - Priyanto, Tri Hardi; Muslih, Rifai; Mugirahardjo, Herry; Bharoto, Bharoto; Insani, Andon; Muzzakiy, Muzzakiy (UI Scholars Hub, 2018)
Theoretically, the preheating temperature refers to the start martensite temperature (Ms), and the martensite transformation can be considered as the conservation of the invariant habit-plane in the lattice structure. The habit-plane is the interface plane between austenite and martensite as measured on a macroscopic scale. From the calculation, Ms = 252 °C. The martensite formation can be affected by temperature or stress treatment. In this experiment, temperature treatment was conducted. The sample was treated at 250 °C ± 10 °C. Before and after the pre-heat treatment, the sample was characterized using the neutron diffraction method. BATAN’s Texture Diffractometer (DN2) with a neutron wavelength of 1.2799Å was used to characterize the sample. Analysis of the crystal structure showed that there are three phases before the preheating. The lattice parameters (a) obtained were as follows: for the -phase, a = 2.8501 ± 0.0004 Å; for the α’-phase, a= b =2.517 ± 0.003 Å, and c= 3.581 ± 0.002 Å; for the -phase, a= 3.5884 ± 0.0004 Å, Rwp = 17.94%, and  = 1.33. After preheating, only the -phase appears with a = 3.5830 ± 0.0005 Å, Rwp = 26.03%, and  = 1.17. The orientation distribution function is modeled by the sample symmetrization model based on triclinic to orthorhombic sample symmetry. It shows that, before being preheated, the -phase has 100with texture index (F2 ) between 0.701 m.r.d. to 3.650 m.r.d., the α-phase has a texture index between 0.923 m.r.d. to 1.768 m.r.d., and the ’-phase has a texture index between 0.910 m.r.d. to 1.949 m.r.d. After being preheated, the -phase also has 100with a texture index between 0.846 m.r.d. to 3.706 m.r.d. It can be concluded, that because of the high preheating temperature, a phase change from martensite to austenite occurred that allowed the sample to be welded easily. After preheating, the -phase has the same cubic type orientation 100, and the texture index is nearly the same as that before preheating, with not martensite present.